2019
DOI: 10.1128/aac.01975-19
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Mammalian Serum Amyloid A1 against Candida albicans

Abstract: Mammalian serum amyloid A (SAA) is a major acute phase protein that shows a massive increase in plasma concentration during inflammation. In the present study, we demonstrate that the expression of mouse SAA1 in serum was increased when infected with Candida albicans, a major human fungal pathogen, in a systemic infection model. We then set out to investigate the antifungal activity of SAA proteins against C. albicans. Recombinant human and mouse SAA1 (rhSAA1 and rmSAA1) were expressed and purified in Escheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…On the other hand, upon fungal infection, the host has a number of defense strategies, including secreting AMPs, "nutritional immunity," and producing antibodies through adaptive immunity to clear invading fungal pathogens (15). Mammalian SAA1 is a major acute-phase protein that has antimicrobial activity against both bacteria and fungi (5,7). In the present study, we set out to investigate the antifungal mechanism of human SAA1 against C. albicans.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, upon fungal infection, the host has a number of defense strategies, including secreting AMPs, "nutritional immunity," and producing antibodies through adaptive immunity to clear invading fungal pathogens (15). Mammalian SAA1 is a major acute-phase protein that has antimicrobial activity against both bacteria and fungi (5,7). In the present study, we set out to investigate the antifungal mechanism of human SAA1 against C. albicans.…”
Section: Discussionmentioning
confidence: 99%
“…We previously found that rhSAA1 binds to the cell surface of C. albicans and disrupts membrane integrity (7). Interestingly, unlike most membrane-disrupting AMPs, human SAA1 is hydrophilic and negatively charged (16), and native SAA1 often exists as a hexamer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations